A Study on the Twist Loss in Weft Yarn during Air Jet Weaving. Issue 4 (December 2017) - Umair, Muhammad; Shaker, Khubab; Nawab, Yasir; Rasheed, Abher; Ahmad, Sheraz
Air jet weaving is considered to be the most advanced method of fabric production in which weft yarn is inserted with air pressure. But due to very high pressure some of yarn twist is lost during fabric production. This affects the strength of the yarn in general and quality of the fabric in particular. This study deals with the parameters affecting twist loss in weft yarn during air jet weaving. The subsequent effect of twist loss on the mechanical properties of yarn as well as fabric is also studied. A total of twenty-four different fabric samples were produced to consider the effect of yarn linear density, material, weave design and fabric width on the twist loss in picking and receiving sides of the woven fabric. The 100% cotton and polyester-cotton (PC) ring spun yarns having linear densities 37, 27 and 15 tex were used to produce fabrics in two different weaves i.e. 1/1 plain and 3/1 twill weave. In addition, two different fabric widths i.e. 121 and 100 cm were produced. The twist loss increases with increase in the fineness of yarn. In PC yarns twist loss percentage was higher as compared to cotton yarns. Twist loss in wider width was higher as compared to smaller widths of the fabric, while the effect of weave design was negligible.